Table of Content - - (Journal of natural sciences, life and applied sciences, 2023)
Table of Content: 1. Producing a sweetened drink for diet using invertase enzyme extracted from some Iraqi dates Dr. Zahraa S. Al-Garawi, Mr. Ahmed R. Ahmed, Mr. Ahmed M. Hussein, Mrs. Naba` S. Nasir 2. The role of modern construction methods in environmental sustainability at the project site Mrs. Ibtisam Marshod Alharbi 3. Assessment the horizontal micro-tunnelling discharge for torrents in Buraydah city, Al-Qassim region Mr. Fihan Mamdouh Saud Al-Rashidi 4. Measurements of trees in the city of Abha using lidar technology by smart phones Mrs. Eman Saeed Al-Shahrani, Co-Prof. Sulafa Haj Al-Safi 5. Evaluation of Industrial Waste in the Paints Industry Sector: Khartoum North Industrial Area, Dr. Mona Ali Mohamed Ahmed